2019
DOI: 10.32598/bcn.9.10.395
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithmic Model of Decision Making in the Human Brain

Abstract: Introduction:One of the interesting topics in neuroscience is problem solving and decisionmaking. In this area, everything gets more complicated when events occur sequentially. One of the practical methods for handling the complexity of brain function is to create an empirical model. Model Predictive Control (MPC) is known as a powerful mathematical-based tool often used in industrial environments. We proposed an MPC and its algorithm as a part of the functionalities of the brain to improve the performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…These studies were performed under the supraphysiological influence of testosterone in PFC in testosterone-induced impulsivity rat model. The PFC was chosen because of its well-studied role in motor control ( Robbins and Dalley, 2017 ; Sholler et al, 2020 ) decision making ( Hiser and Koenigs, 2018 ; Saberi Moghadam et al, 2019 ), and emotional processing and regulation ( Dixon et al, 2017 ). Our previous study also indicated that PFC plays a significant role in testosterone-mediated impulsivity ( Agrawal et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…These studies were performed under the supraphysiological influence of testosterone in PFC in testosterone-induced impulsivity rat model. The PFC was chosen because of its well-studied role in motor control ( Robbins and Dalley, 2017 ; Sholler et al, 2020 ) decision making ( Hiser and Koenigs, 2018 ; Saberi Moghadam et al, 2019 ), and emotional processing and regulation ( Dixon et al, 2017 ). Our previous study also indicated that PFC plays a significant role in testosterone-mediated impulsivity ( Agrawal et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mutual communication between the prefrontal cortex and hippocampus creates a closed circuit to produce a decision. [9] Besides the prefrontal cortex and hippocampus, other parts of the brain also affect the decisionmaking process, and we have yet to know their mechanism. With quantum physics, we might better understand the cooperation among different components in the brain by applying a quantum model to the complicated and somewhat unpredictable patterns of neural signals.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroeconomics being a multi-disciplinary field is considerably associated with different fields of neuroscience, ranging from neuropsychology, computational and theoretical neuroscience, to cognitive and behavioral neuroscience [ 1 ]. Cognitive and behavioral neuroscience involves the neural mechanisms of mental and behavioral activities, or, more generally, the relationships among the brain, the mind, and action [ 6 , 7 , 23 ].…”
Section: The Relationship Of Neuroscience Economics and Psychology Wi...mentioning
confidence: 99%
“…The process of decision-making is dependent on the prefrontal cortex and hippocampus and is done in four steps; firstly, sensory inputs produce an initial stimulus, which excites a set of hippocampal neurons, secondly, another set of secondary stimuli arrives within the hippocampus where the stimulus neuron response is then produced as initial information. Thirdly, this initial information is delivered to the prefrontal cortex, which then determines the additional information needed and retrieves it from the hippocampus [ 23 ]; X.-J. [ 7 ]; lastly, the prefrontal cortex reaches a proposed controlling process.…”
Section: Neuroanatomy Of Decision Makingmentioning
confidence: 99%